Growth Plan In Operational Design Management For Pt. Traffic Light Jaya - Kristanto, Heru; Marlitta, Cheryl (Riviera Publishing, 2022)
Traffic congestion is followed via way of means of more and more site visitors injuries. These are ruled via way of means of bike injuries, which additionally account for the very best part of fatalities and essential injuries. Careless riding and unruly conduct via way of means of drivers are the primary reasons of injuries in Indonesia. Penelitian ini bertujuan untuk a coordinated attempt which can also additionally alleviate a metropolis’s congestion is deemed necessary, specially in tackling busy and complicated intersections on the middle of the trouble to lessen losses. Research is carried out using qualitative research. It was concluded that The company must have good marketing and operational strategies to get more customers and maintain the business in order to keep it disrupting the times. The future challenge is very challenging for this business to set up a new strategy to meet market demands and globally transform. With the presence of a 24-hour hotline to receive customer complaints I feel is one form of responsibility from the company. Building a laboratory seems to be needed in the near future given the many demands in the three cities as a preliminary experiment. It is hoped that with good management operations, this business can dominate and be irreplaceable, given the purpose of establishing this company is to be a solution to the bottleneck and effectiveness of the government budget